امت مسلمہ کے فرقہ ورانہ مسائل کا حل سیرت طیبہ کی روشنی میں: The solution to the sectarian problems of the Muslim Ummah in the light of Sira-e-Taiba - Dr Sada Hussain Alvi; Muhammad Ishfaq (International Research Journal of Arabic and Islamic Studies, 2022)
The Muslim nation (Ummah) has also been named Ummat-e-Wusta in Holy Quran. It carries the message of moderation, serenity and unity among humans. This Ummah can seek proper guidance in the seerah of Holy Prophet (PBUH) regarding their individual and collective problems. The whole life of Holy Prophet (PBUH) is a beacon of light for the Ummah. So, first of all we should find the major problems confronting the Ummah then we will try to understand the solution of these problems with the help of Prophet’s (PBUH) life. Muslim Ummah has dispersed on basis of language, creed and jurisprudence. Such sectarian differences have led this Ummah to severe controversies and proxy wars among different countries. Ethnic differences have also affected a large part of the Muslim world. Hate-based lectures, biased speeches and writing have set this Ummah in hand to hand fight. The syllabus of academic institution is deprived of subjects of Seerah of Prophet (PBUH). On the other hand, there are many things in syllabus that lead to sectarianism and improve racism. Another important issue is the aggressive and ignorant so-called religious leadership that leads the masses.In short, there is the proper guidance in the seerah of Holy Prophet (PBUH) regarding solution of the creed and jurisprudent differences, linguistics and ethical variances, hate and love, the principles of training, leadership and especially religious leadership, education and mutual social relationship. All of this is in the guidance of the Prophet’s (PBUH) life.